Final comments: looking to the future - Fradley, M; Sheldrick, N (Cambridge University Press, 2017)
We thank Sarah Parcak et al. for their response to our paper, for engaging in this important debate and for clarifying a number of points regarding Parcak et al. (2016), and for raising some important questions concerning the methods and objectives of the EAMENA project. We can, however, only comment on what was presented in their original article and address, in these brief final remarks, a few of the points raised in their response.